ANALISIS LITERASI SAINS TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK KELAS IV SEKOLAH DASAR - Silvia Indras Wati; Farida Nur Kumala; Arnelia Dwi Yasa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Scientific literacy and critical thinking skills are essential competencies for elementary school students in the global era. Scientific literacy is not only the mastery of scientific concepts, but also the ability to use that knowledge to understand phenomena and make evidence-based decisions, which are important foundations in developing students' critical thinking skills. This study aims to analyze the relationship between scientific literacy and critical thinking skills in fourth-grade students at SDN Ciptomulyo 1 Malang. The problem identified in this study is the need to improve students' critical thinking skills, especially in the aspects of evaluation and reflection on complex information. The method used is qualitative with a population of all parties related to learning in fourth grade, and the research subjects consisted of teachers and 24 fourth-grade students who were selected purposively. Data were collected through interviews, observations, and documentation. Data analysis was carried out through data reduction, narrative and tabular presentation, classification, source triangulation, and drawing conclusions. This research is relevant and urgent to conduct because scientific literacy and critical thinking skills are highly needed today, especially in facing the challenges of the 21st century. The results show that students with high scientific literacy tend to have good critical thinking skills, especially in analysis, interpretation, and evidence- based decision-making. Research findings show that students with high scientific literacy scores tend to have high critical thinking scores. However, their ability to evaluate and reflect on complex information still needs improvement. The study's conclusions confirm that scientific literacy is an important foundation for developing critical thinking skills, supported by interactive learning methods and the role of teachers. Consequently, schools need to actively integrate scientific literacy into their learning, develop innovative learning methods, and provide adequate learning resources to enhance students' critical thinking skills.